Pengembangan Aplikasi Pembuat Keputusan ‘Make Your Choice’ Menggunakan Model Waterfall - Ilyas, Frennandi Ade; Ainurrohim, Reji; Ma'ani, Muhammad Lizam; Jasmiati, Desi; Mulyati, Sri; Nirmala, Endar (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2021)
Lately, many students in Indonesia have difficulty knowing their interests and future goals, resulting in problems in determining which majors to choose. For that we need an efficient and sophisticated problem solving. MYC (Make Your Choice) is a web-based application that can help provide a choice to the user based on the interests or habits of the user. This application is made with the PHP 7 programming language, using the Laravel framework with DBMS MySQL 10 and the Fuzzy logic method which aims to assist in the selection of major decisions according to interests and talents based on test results or available questions, in order to facilitate counseling between students and teachers or guardians. the student. The design of this system will use the Waterfall process model, then in the visualization of the model using Use Case Diagrams and Activity Diagrams. Based on the results of use and testing, this application runs very well. The results of using this application students or new students can see potential college opportunities and business opportunities and reduce the potential for errors in the selection of majors. The features available in this application include information from each department, job opportunities and business opportunities and also print election results.